2016
DOI: 10.3389/fpls.2016.01788
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Photosynthetic Characteristics and Quality Improvement of Purple Cabbage under Different Combinations of Monochromatic Light

Abstract: Light is essential for plant growth. Light intensity, photoperiod, and light quality all affect plant morphology and physiology. Compared to light intensity, photoperiod, little is known about the effects of different monochromatic lights on crop species. To investigate how different lighting conditions influence crops with heterogeneous colors in leaves, we examined photosynthetic characteristics and quality (regarding edibility and nutrition) of purple cabbage under different combinations of lights. Eight di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Abnormal plant morphology and reduced photosynthetic rate were observed when lettuce was exposed to red LED light alone (Goins et al, 1998;Wang et al, 2009). In a further study, blue LED alone was found to reduce the photosynthetic rate of purple cabbage (Ziwei) (Yang et al, 2016). This suggested that monochromatic red or blue light would not meet the requirements for healthy plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal plant morphology and reduced photosynthetic rate were observed when lettuce was exposed to red LED light alone (Goins et al, 1998;Wang et al, 2009). In a further study, blue LED alone was found to reduce the photosynthetic rate of purple cabbage (Ziwei) (Yang et al, 2016). This suggested that monochromatic red or blue light would not meet the requirements for healthy plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…For each lighting source of the 27 combinations, white LEDs and XTRASUN LEDs, luminous flux (Φ) (expressed in lm) and the total electric power (P) (expressed in W) were all recorded. Then, with these measurements we determined the luminous efficacy (η) (expressed in lm W −1 ) using Equation (1). The minimum illumination level (Ev) was calculated dividing the value of Φ by the surface (S) (1.2 m 2 ) (expressed in lx) and the limit value of energy efficiency (VEEI) (expressed in W m −2 ) was then calculated using Equation (2) following the methodology established by Hidalgo et al [20].…”
Section: Technical Parameters Of the Lampsmentioning
confidence: 99%
“…Light is one of the most important environmental regulators for the growth of crop species since it provides essential energy input and triggers various signaling pathways for the dynamic growth regulation of crops [1]. In this sense, plant species have evolved photoreceptors to sense the light environment and adjust to changing environmental conditions through the modulation of cellular processes [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illumination is a powerful environmental stimulus with impacts on a wide range of plant metabolic processes [1]. The ability of plants to sense and respond to light depends on their photosynthetic pigments and photoreceptors that absorb different wavelengths of the light [2].…”
Section: Introductionmentioning
confidence: 99%